2015
DOI: 10.1016/j.gecco.2015.07.003
|View full text |Cite
|
Sign up to set email alerts
|

The demography of Atelopus decline: Harlequin frog survival and abundance in central Panama prior to and during a disease outbreak

Abstract: a b s t r a c tHarlequin frogs (Bufonidae: Atelopus) are a species-rich genus of Neotropical toads that have experienced disproportionately severe population declines and extinctions caused by the amphibian chytrid fungus Batrachochytrium dendrobatidis (Bd). The genus Atelopus is of high conservation concern, but relatively little is known about the population dynamics and life history of the majority of species. We examined the demography of one population of Atelopus zeteki and two populations of A. varius i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 34 publications
0
22
0
4
Order By: Relevance
“…En la población estudiada de Atelopus balios la proporción de machos/hembras fue de 8.6:1. Siendo similar a lo reportado en Atelopus varius, donde se registró una proporción de 8.08:1 (14). Pero difieren de lo registrado en Atelopus spumarius donde fue de 4.1:1 (15), en Atelopus zeteki que fue de 2.24:1 (14), en Atelopus cruciger que fue de 2:1 (16), y en contraste para Atelopus laetissimus que fue de 24.5:1 (17).…”
Section: Discussionunclassified
“…En la población estudiada de Atelopus balios la proporción de machos/hembras fue de 8.6:1. Siendo similar a lo reportado en Atelopus varius, donde se registró una proporción de 8.08:1 (14). Pero difieren de lo registrado en Atelopus spumarius donde fue de 4.1:1 (15), en Atelopus zeteki que fue de 2.24:1 (14), en Atelopus cruciger que fue de 2:1 (16), y en contraste para Atelopus laetissimus que fue de 24.5:1 (17).…”
Section: Discussionunclassified
“…Recent work has shown that adult virulence in several frog populations has not decreased even after 20 years of Bd presence (Voyles et al ). Already, frog demography has been implicated as an important factor for population persistence in the face of Bd with frog species where adults move away from breeding waters being more resistant to population declines (Lips et al ; McCaffery et al ), and frogs in habitats with multiyear larvae having more severe epidemics because the older stages maintain high levels of infection that then spill over to infect other stages and species (Medina et al ; Hite et al ). The assortativity of mixing clearly has important implications for disease transmission across stages, and our model suggests that it could also have implications for the maintenance of high virulence in different age stages.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work has shown that adult virulence in several frog populations has not decreased even after 20 years of Bd presence (Voyles et al 2018). Already, frog demography has been implicated as an important factor for population persistence in the face of Bd with frog species where adults move away from breeding waters being more resistant to population declines (Lips et al 2006;McCaffery et al 2015), and frogs in habitats with multi-year larvae having more severe epidemics because the older stages maintain high levels of infection that then spill over to infect other stages and species (Medina et al 2015;Hite et al 2016). Changes in the assortativity of mixing clearly has important implications for disease transmission across stages, and our model suggests that it could also have implications for the maintenance of high virulence in different age stages.…”
Section: Discussionmentioning
confidence: 99%